INFLUENCE OF DIABETES MELITUS, BMI, AND HBA1C IN HIGH GRADE PROSTATE CANCER - hadibrata, exsa; Danarto, H R (Indonesian Journal of Urology, 2017)
Objective: This study aims to determine the effect of diabetes mellitus (DM) and body mass index (BMI) on the risk of prostate cancer and high grade prostate cancer. Materials & method: This study is a retrospective observational study with cross-sectional design, using secondary data to determine the relationship of diabetes mellitus, body mass index and HbA1c levels with the degree of differentiation histopathologic prostate cancer. Data were analyzed using Chi-Square test, T-test and Man Whitney test with a confidence level of p<0.05 and a=0.05. Results: There are 78 samples diagnosed with prostate cancer. A total of 12 (15.4%) samples are diabetes mellitus, 18 (22.9%) samples classified as body mass index more than 23.4 (5.1%) samples have elevated levels of HbA1c levels >6.5. On histopathologic examination, it was found as many as 45 (57.7%) samples with high grade prostate cancer, as much as 9 (11.5%) samples with moderate grade prostate cancer, and as many as 24 (30.8%) samples with low grade prostate cancer. In bivariate analysis diabetes mellitus, BMI>23, and HbA1c level relationship with high grade prostate cancer is not statistically significant with p>0.05. Conclusion: There were no statistically significant relationship between diabetes, BMI and increased levels of HbA1c with high grade prostate cancer.